Pengaruh Pendidikan Karakter, Motivasi Belajar dan Aktivitas Belajar terhadap Prestasi Belajar pada Siswa Sekolah Dasar - Emy Emy; Margono Mitrohardjono (Jurnal Syntax Transformation, 2021)
Learning success is a change in behavior as a result of learning that covers the cognitive, affective, and psychomotor fields. Therefore, in the assessment of learning outcomes, the role of instructional examinations that contain formulation of abilities and behaviors desired by students becomes an important element as a basis and reference for assessment. Learning success is also the success of students in forming competencies and achieving goals as well as the success of teachers in guiding students in learning. Data analysis and hypothesis testing are done using simple regression analysis to partially test hypotheses, and multiple regression analysis to test hypotheses simultaneously. This research has the goal of knowing and testing the influence of Character Education, Learning Motivation and Learning Activities on Student Learning Achievement, both partially and simultaneously, research shows that character education partially or simultaneously positively and significantly affects learning achievement with a significance level of 0.029. Learning motivation partially and simultaneously has a positive and significant effect on learning achievement with a significance level of 0.001. Learning activities partially positively and significantly affect with a significance level of 0.172. Learning motivation and learning activities simultaneously have a positive and significant effect on learning achievement, based on the results of statistical calculations. The value of F is 91.931 while the table F value for the sample number is 54 (0.95, 3; 54) from (2.78), so the value of F calculates greater than F of the table. Lastly, character education, learning motivation and learning activities simultaneously have a positive and significant influence on learning achievement. Subsequent research suggested it could use a larger sample number by involving students, parents of students and teachers